THE EFFECT OF KNOWING ENGLISH LANGUAGE IN LEARNING OTHER SUBJECTS - Dilrabo Safarova Kholmurodovna (Western European Studies, 2023)
Mastering the English language is not just about communication; it also offers significant advantages in learning other subjects. In this article, we will explore how learning English can enhance students’ understanding and performance across various academic disciplines. Drawing upon research and expert opinions, we will discuss the cognitive benefits, improved critical thinking skills, and expanded access to resources that come from learning English.
Keywords: Researches; second language; subjects; science